Fast electron energy transport in solid density and compressed plasma - Norreys, P; Batani, D; Baton, S; Beg, F; Kodama, R; Nilson, P; Patel, P; Perez, F; Santos, J; Scott, R; Tikhonchuk, V; Wei, M; et al. (Institute of Physics Publishing, 2014)
We provide a review of selected experiments on fast electron transport in solids and plasmas following laser-matter interaction at relativistic intensities. Particular attention is given to precise measurements of intense laser pulses, fast electron energy transfer and the mean kinetic energy of the fast electrons. We discuss in detail mechanism of fast electron energy loss in solid and warm dense targets. We show that stopping due to resistive electric field and collimation due to resistive magnetic field play significant roles in fast electron dynamics. It has also been shown that reducing the size of the target can significantly affect the K production from the targets. The use of reduced-mass target can also increase temperature up to 1keV level, which provides an excellent platform for fast electron transport without assembling the fuel. The pre-pulse is a significant issue in fast ignition for fast electron coupling to the compressed core. Indeed, we have shown using a variety of targets that the laser pre-pulse can significantly reduce transfer of energy farther into the target. In this article, we show that a significant progress has been made in understanding the critical issues of fast electron transport pertinent to fast ignition (FI). This understanding will facilitate a better target design for large scale FI integrated experiments when laser facilities become available. © 2014 IAEA, Vienna.